Menggugat Hukum yang Bias Gender - Zairin Harahap (Fakultas Hukum Universitas Islam Indonesia, 2003)
Law put women in inequitable position. One of the reasons is strong patriarchy culture in our community up to this time. Such culture out women in weak and domestic position and the positioning is on the basis of destiny where gender issue is merely connoted with sex.